Epidemiological Profile of Gastric Adenocarcinoma in Morocco: Evolution and Risk Factors - Khali, Abdellah Ben; Ouazzani, Houria Chahed; Soulaymani, Abdelmajid; Quyou, Ali (European Scientific Journal, ESJ, 2019)
Background: Gastric cancer (GC) remains a public health issue despite the global incidence decrease over the last decades. GC is the third leading cause of cancer-related death worldwide and it is still of poor prognosis due to its late detection. This paper focuses on determining the sociodemographic and progressive characteristics of patients who presented gastric adenocarcinoma in the absence or in the presence of the bacterium Helicobacter pylori at the service of Hepato-Gastroenterology at the University Hospital of Rabat in Morocco. Methods: To evaluate the epidemiological characteristics of gastric adenocarcinoma in the absence or in the presence of the bacterium Helicobacter pylori, a retrospective study was conducted on cases admitted at the Hepato-Gastroenterology department (University Hospital, Avicene Rabat) between 2000 and 2010 to support gastric adenocarcinoma. Results: 240 cases of GC were recorded with an average of 22 cases per year, which represents 77% of all gastric cancers identified. Male gender is most affected. The frequency of appearance of ADK in the absence of the bacterium Hp is 82% (196 cases). It is 18% (44 cases) in the presence of Hp. During the study period, 99 deaths were recorded: 81 cases in the presence of the bacterium Helicobacter pylori, 18 cases of death in the absence of Hp. The lethality rate was higher in the male sex, either in the presence or absence of Hp. Conclusions: Management of GC additionally to early diagnosisrepresents effective preventive and therapeutic methods of GC.